The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/wps.20295
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from unintended consequences about erasing the stigma of mental illness

Abstract: Advocates and scientists have partnered to develop and evaluate programs meant to erase the egregious effects of the different forms of stigma. Enough evidence has been collected to yield lessons about approaches to stigma change. Some of the most insightful of these lessons emerge from unintended consequences of good intentioned approaches, and are the focus of this paper. They include the limited benefits of education especially when compared to contact, beating stigma is more than changing words, beware pit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
140
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(162 citation statements)
references
References 58 publications
2
140
0
3
Order By: Relevance
“…For those with FND, there is a stigma ascribed to having mental illness as the cause of their symptoms. Stigma is a cognitive framing or worldview that leads to stereotyping, prejudice, and unjust discriminatory acts (26). With stigma, negative evaluations lead to negative emotions.…”
Section: Introductionmentioning
confidence: 99%
“…For those with FND, there is a stigma ascribed to having mental illness as the cause of their symptoms. Stigma is a cognitive framing or worldview that leads to stereotyping, prejudice, and unjust discriminatory acts (26). With stigma, negative evaluations lead to negative emotions.…”
Section: Introductionmentioning
confidence: 99%
“…Although the research of mental illness stigma has found that elevated anxiety and fear are associated with increased levels of mental illness stigma (e.g., Angermeyer et al, 2010;Corrigan, 2016), research of other types of stigma offers results similar to those of the current study. For example, in his study of empathy and personal distress in the context of HIV/AIDS related stigma, Olapegba (2010) found that higher levels of personal distress led to higher levels of emotional concern, which then led to lower levels of stigma.…”
Section: Mental Illness Stigmasupporting
confidence: 74%
“…beliefs, about mental illness that lead to the public's fear, rejection, avoidance, and discrimination against people who have a mental illness (Corrigan, 2016;Parcesepe & Cabassa, 2013). Similar to other forms of bias and prejudice, such as racism and sexism, the public stigma of mental illness matters because it "sets the context in which individuals in the community respond to the onset of mental health problems, clinicians respond to individuals who come for treatment, and public policy is crafted" (Pescosolido et al, 2010(Pescosolido et al, , p. 1324.…”
Section: Types Of Mental Illness Stigmamentioning
confidence: 99%
See 2 more Smart Citations